Simulink as an advanced tool for analysis of dynamical electrical systems - Osowski, Stanislaw (Publishing House of Lviv Polytechnic National University, 2011)
Simulink is a powerful toolbox of Matlab, very useful in analysis of dynamical systems. The paper presents the application of Simulink/Matlab in analysis of the dynamical electrical systems. It will be shown that it is an ideal tool for quantitative and qualitative analysis of electrical and electronic networks. Its usefulness will bе shown on the example of modeling the 3-phase induction machine and a power system. The non-classical examples of using Simulink include the analysis of nonlinear system in the state space, determination of the stability of the equilibrium points as well as optimization of the electrical circuit. It should be mentioned that nowadays version of Simulink allows also to model the electrical networks directly on the basis of circuit structure (the specialized library SimElectronics) without describing explicitly the circuit by the system of equations. Simulink є потужним набором інструментів Маtlab-у, дуже корисним при аналізі динамічних систем. У статті показано застосування Simulink/Matlab до аналізу динамічних електричних систем. Показано, що це є ідеальним засобом для чисельного та якісного аналізу електричних та електронних мереж. Його ефективність показано на прикладі моделювання 3-фазної індукційної машини та енергетичної системи. Некласичні приклади використання Simulink-у включають аналіз нелінійної системи у просторі станів, визначення стійкості станів рівноваги, а також оптимізацію електричного кола. Слід зауважити, що сучасна версія Simulink-у дозволяє моделювати електричні мережі безпосередньо на підставі структури кола (спеціалізована бібліотека SimElectronics) без явного опису кола системою рівнянь.
Simulink як ефективний інструмент аналізу динамічних електричних систем
Keywords: Dynamical electrical systems; simulation; numerical methods; state space analysis